Work Competency and Social Work Environment to Improve Employee Performance at PT Pertamina - Hanifa Yasin; Julita Julita (International Journal Of Economics Social And Technology, 2022)
Performance is a result of work achieved by a person in carrying out the tasks assigned to him based on skill, experience, seriousness and time. There are several factors that affect performance, namely, skills, competencies possessed, motivation, and individual commitment. This study aims to determine the ability of work and social work environments to improve employee performance at PT. Pertamina (Persero) Marketing Operation Region 1 HR Unit of Sumbagut. The research approach used is the type of associative research. The sample used was 60 people. Data collection techniques in this study used a questionnaire. Data analysis techniques in this study use validity, reliability, multiple linear analysis, and data processing in this study using the SPSS software program (Statistical Package for the Social Science) version 18.00 for windows. The results of this study prove that improving employee performance is influenced by work competence and the social work environment. The results of SPSS partially obtained at 0.013, which means that work competence can improve employee performance. while the social work environment is 0.029 which means that it is not a factor in improving employee performance. work competence can improve employee performance. While the social work environment cannot improve employee performance.